Letter to Jane Tolmach from John T. Conlan - John T. Conlan:::::: (1970)
A letter to Jane Tolmach from Supervisor John T. Conlan informing her of the time and date of the next Environmental Impact Study ad hoc Citizens Advisory Committee. Includes mention of a reiteration of the noise and air pollution studies and a presentation on environmental and aesthetic considerations.